Thermophysical property models for lunar regolith. Issue 5 (1st March 2016) - Schreiner, Samuel S.; Dominguez, Jesus A.; Sibille, Laurent; Hoffman, Jeffrey A.
Highlights: We construct a set of thermophysical property models for lunar regolith. Data for lunar regolith material properties from over 25 sources is collected. The data comes from a range of Apollo samples and lunar simulants. Data from molten regolith simulants is included to extend beyond existing models. Separate regression models are fit to the data for Mare and Highlands regolith. Abstract: We present a set of thermophysical property models for lunar regolith. Data from over 25 sources in the literature are integrated and fit with regression models for the following properties: composition, density, specific heat, latent heat of melting/fusion, thermal conductivity, electrical conductivity, optical absorption length, Gibbs Free Energy and Enthalpy of Formation. The models are based on data from Apollo samples and high-temperature molten regolith simulants, extending significantly beyond existing models in the literature. Furthermore, separate regression models are presented for Mare and Highlands regolith to demonstrate the effect of composition and to allow the models to be tailored to a wide range of applications. These models can enable more consistent, informed analysis and design of lunar regolith processing hardware and can also support lunar geological simulations. In addition to regression models for each material property, the raw data are presented to allow for further interpretation and fitting as necessary.